Estudo do efeito dos flares na amplitude dos modos acústicos solares - Vanessa Graziela Teixeira (2021)
Helioseismology makes it possible to study the structure and dynamics of the Sun by observing and analyzing the acoustic modes propagating inside it. Solar flares, in turn, are a sudden increase in brightness observed on the surface of the Sun originating from the reconnection of magnetic field lines, which release a large amount of energy in a short period of time. It is believed that some of this energy may contribute to the excitation of acoustic modes, thereby increasing their amplitudes. The aim of this work is to investigate whether and how solar flares affect the oscillation modes on the Sun. First, one of the most energetic flares ever recorded in recent decades, which occurred on October 28, 2003, was analyzed using data from the MDI (Michelson Doppler Imager) instrument aboard the SOHO (Solar and Heliospheric Observatory). Correcting for the line-of-sight effect of each region analyzed, no amplitude enhancement effect due to the flare was found, contrary to the results obtained by Maurya et al. (2009) using data from the GONG (Global Oscillation Network Group) instrument. Next, a class X2.1 flare was analyzed using helioseismic data from the Helioseismic and Magnetic Imager (HMI) instrument aboard the Solar Dynamics Observatory satellite (SDO/NASA), where no clear effect of the flare on the amplitude of the modes was also found. To conclude, a comparative statistical study of the mode amplitude variation was done by performing, mode by mode, the difference between the mean relative amplitudes of regions with and without flare whose mean magnetic field was similar. No variations greater than 20 % were found between the mean relative amplitudes. The results obtained showed that the average relative amplitude of regions with flare is smaller than that of regions without flare for most of the frequency values, a result contrary to what was expected. It was shown that this is due to the effect of the active regions present in larger numbers in the vicinity of the flare regions.